The Imagination to Listen: Reflections on a Decade of Zapatista Struggle - Mora, Mariana (Social justice, 2003)
Part of a special section on the intersection of ideologies of violence. The writer examines the Zapatista National Liberation Army (EZLN) uprising against the Mexican government in the state of Chiapas, noting that in 2003 the EZLN movement it aligned itself with anti-neoliberal social movements in Mexico and around the globe. She outlines the central interventions of the EZLN movement, including a politics of listening, which transforms cultural politics connected to radical democratic practices; claims to dignity and control over the right to alter traditions as central to establishing respect for diversity; and autonomy as a disconnection from state procedures and as a condition for inclusion.